Draft Eighth Plan 1990-95 and Draft Annual Plan 1991-92 Vol-III Government of Tripura - Planning Commission (Planning Commission, 1991)
Integrated Rural Development Programme (IRDP) is a Centrally Sponsored Continuing Programme Under Special Programme of the Rural Development since the beginning of 6th Plan as a part of the All India Programme. A single agency namely Tripura Rural Development Agency(TRDA) was operating through out the State From 2.10.1980 to 31.8.1982 for IRDP along with an going Scheme under SFDA. From 1.9.82 separate establishments were set up in the 3(three) Districts (District Rural Development Agency).
Government of Tripura